Multiple populations in integrated light spectroscopy of intermediate-age clusters. (26th August 2019) - Bastian, Nate; Usher, Christopher; Kamann, Sebastian; Lardo, Carmela; Larsen, Søren S; Cabrera-Ziri, Ivan; Chantereau, William; Martocchia, Silvia; Salaris, Maurizio; Schiavon, Ricardo P; Asa'd, Randa; Hilker, Michael
ABSTRACT: The presence of star-to-star light-element abundance variations (also known as multiple populations, MPs) appears to be ubiquitous within old and massive clusters in the Milky Way and all studied nearby galaxies. Most previous studies have focused on resolved images or spectroscopy of individual stars, although there has been significant effort in the past few years to look for multiple population signatures in integrated light spectroscopy. If proven feasible, integrated light studies offer a potential way to vastly open parameter space, as clusters out to 10s of Mpc can be studied. We use the Na D lines in the integrated spectra of two clusters with similar ages (2–3 Gyr) but very different masses: NGC 1978 (∼3 × 10 5  M⊙ ) in the Large Magellanic Cloud and G114 (1.7 × 10 7  M⊙ ) in NGC 1316. For NGC 1978, our findings agree with resolved studies of individual stars that did not find evidence for Na spreads. However, for G114, we find clear evidence for the presence of multiple populations. The fact that the same anomalous abundance patterns are found in both the intermediate age and ancient globular clusters lends further support to the notion that young massive clusters are effectively the same as the ancient globular clusters, only separated in age.